If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying logx + log(x + -4) = log(17x) Reorder the terms: glox + glo(-4 + x) = log(17x) glox + (-4 * glo + x * glo) = log(17x) glox + (-4glo + glox) = log(17x) Reorder the terms: -4glo + glox + glox = log(17x) Combine like terms: glox + glox = 2glox -4glo + 2glox = log(17x) Remove parenthesis around (17x) -4glo + 2glox = glo * 17x Reorder the terms for easier multiplication: -4glo + 2glox = 17glo * x Multiply glo * x -4glo + 2glox = 17glox Solving -4glo + 2glox = 17glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-17glox' to each side of the equation. -4glo + 2glox + -17glox = 17glox + -17glox Combine like terms: 2glox + -17glox = -15glox -4glo + -15glox = 17glox + -17glox Combine like terms: 17glox + -17glox = 0 -4glo + -15glox = 0 Factor out the Greatest Common Factor (GCF), '-1glo'. -1glo(4 + 15x) = 0 Ignore the factor -1.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(4 + 15x)' equal to zero and attempt to solve: Simplifying 4 + 15x = 0 Solving 4 + 15x = 0 Move all terms containing g to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 15x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 15x = 0 + -4 15x = 0 + -4 Combine like terms: 0 + -4 = -4 15x = -4 Add '-15x' to each side of the equation. 15x + -15x = -4 + -15x Combine like terms: 15x + -15x = 0 0 = -4 + -15x Simplifying 0 = -4 + -15x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (1/2-2/7)*3/4 | | 22=1/2x-12x | | 17.5-X+.8=6 | | 8Y-16y-24y= | | 9x+3x+6X=54 | | -7-4/-8-3 | | y=10x+5000 | | 3--8/-7-4= | | 5c^2-3-14c=0 | | 5x+(2+x)=2x-(-6-2x) | | 2x=-6/5 | | (4y^5)/(16u^6y^5-20v^3y^2) | | 3y+14=5y+2 | | e2/x | | (x+2)x(x-3)=0 | | 6y^2+3y=0 | | log9(9^(7/3)) | | 2(x^2-14x+41)=0 | | 2(y-4)-5(y+6)-11= | | sin(x)*cos(x)=1 | | 3a-(9a-5b)= | | 23k=276 | | x/37=14 | | 84=m/47 | | 27m=972 | | 432=36a | | 33=y/16 | | b/22=6 | | x-4x=7 | | m-57=54 | | 211=x+19 | | (4x+5)(10x+5)=0 |